Implementing a combined infection prevention and control with antimicrobial stewardship joint program to prevent caesarean section surgical site infections and antimicrobial resistance: a Tanzanian tertiary hospital experience - Elisa Gentilotti; Pasquale De Nardo; Boniface Nguhuni; Alessandro Piscini; Caroline Damian; Francesco Vairo; Zainab Chaula; Paola Mencarini; Peter Torokaa; Alimuddin Zumla; Emanuele Nicastri; Giuseppe Ippolito (Antimicrobial Resistance and Infection Control, 2020)
Abstract Background Surgical site infections are a leading cause of morbidity and mortality after caesarean section, especially in Low and Middle Income Countries. We hypothesized that a combined infection prevention and control with antimicrobial stewardship joint program would decrease the rate of post- caesarean section surgical site infections at the Obstetrics & Gynaecology Department of a Tanzanian tertiary hospital. Methods The intervention included: 1. formal and on-job trainings on infection prevention and control; 2. evidence-based education on antimicrobial resistance and good antimicrobial prescribing practice. A second survey was performed to determine the impact of the intervention. The primary outcome of the study was post-caesarean section surgical site infections prevalence and secondary outcome the determinant factors of surgical site infections before/after the intervention and overall. The microbiological characteristics and patterns of antimicrobial resistance were ascertained. Results Total 464 and 573 women were surveyed before and after the intervention, respectively. After the intervention, the antibiotic prophylaxis was administered to a significantly higher number of patients (98% vs 2%, p < 0.001), caesarean sections were performed by more qualified operators (40% vs 28%, p = 0.001), with higher rates of Pfannenstiel skin incisions (29% vs 18%, p < 0.001) and of absorbable continuous intradermic sutures (30% vs 19%, p < 0.001). The total number of post-caesarean section surgical site infections was 225 (48%) in the pre-intervention and 95 (17%) in the post intervention group (p < 0.001). A low prevalence of gram-positive isolates and of methicillin-resistant Staphylococus aureus was detected in the post-intervention survey. Conclusions Further researches are needed to better understand the potential of a hospital-based multidisciplinary approach to surgical site infections and antimicrobial resistance prevention in resource-constrained settings.